Multilayer, low‐parasitic, interconnection scheme for advanced submillimetre‐wave GaN circuits. Issue 4 (1st February 2014) - Margomenos, A.; Shinohara, K.; Regan, D.C.; Corrion, A.L.; Brown, D.F.; Tang, Y.; Butler, C.; Schmitz, A.; Robinson, J.F.; Kim, S.; McGuire, C.; Micovic, M.
Abstract : A multilayer, low‐parasitic interconnection scheme for highly scaled GaN high electron mobility transistors is reported. The fabrication process offers three Au interconnects embedded in benzocyclobutene (BCB) dielectric, with an integrated air‐box in the active area in order to minimise the gate parasitic capacitances. With the addition of the air‐box, it is demonstrated that the performance of the BCB encapsulated device is similar to that of a non‐encapsulated device. Furthermore, by utilising the multilayer interconnection scheme a low‐loss (0.75 dB) 3 dB tandem coupler operating from 140 to 220 GHz is demonstrated.